L-carnitine supplementation in the recovery of plasma L-carnitine in patients with heart failure submitted to coronary artery bypass grafting - CRUZ,WANISE M. SOUZA (2018)
Abstract Coronary artery bypass grafting reduces plasma L-carnitine and may impair the production of myocardial energy. L-carnitine supplementation may elevate plasma L-carnitine and increase cardiac mechanical efficiency. The objective of this study was to verify the recovery of preoperative plasma LC in patients with heart failure undergoing coronary artery bypass grafting supplemented with a daily oral dose of 50 mg / kg. Volunteers with ischemic heart failure who underwent surgery were randomized into a supplemented group (A-received 50 mg / kg L-carnitine) or placebo group (B) for 60 days. Supplementation was started on the third postoperative day. The spectrophotometric enzymatic method was used to quantify plasma L-carnitine. In the preoperative period, both groups had plasma L-carnitine adequate to the reference range (18.9-71.1 μM). On the second postoperative day, there was a reduction in plasma L-carnitine in groups A (17.4%) and B (14.4%). In the comparison between the groups, plasma L-carnitine was higher in group A than B in 10º (p = 0.024), 30º (p = 0.001), and 60º postoperative day (p = 0.008). Supplementation of L-carnitine at a daily oral dose of 50 mg / kg in patients with heart failure undergoing coronary artery bypass grafting may recover preoperative plasma L-carnitine within 10 days.